Effects of physical activity and sedentary behaviors on cardiovascular disease and the risk of all-cause mortality in overweight or obese middle-aged and older adults - Zhang, Yongqiang; Liu, Xia (Frontiers in Public Health, 2024)
To respectively explore the relationships of physical activity and sedentary behaviors with cardiovascular disease (CVD) and all-cause mortality risk in middle-aged and older patients with overweight/obesity, and also assess the interaction between physical activity and sedentary behaviors. Data of middle-aged and older adults with body mass index (BMI) ≥25 kg/m2 were extracted from the National Health and Nutrition Examination Surveys (NHANES) database in 2007-2018 in this retrospective cohort study. Weighted univariate and multivariate logistic regression analyses were used to explore the associations between physical activity and sedentary behaviors and CVD; weighted univariate and multivariate COX regression analyses were used to explore the relationships of physical activity and sedentary behaviors with the risk of all-cause mortality. The interaction effect between physical activity and sedentary behaviors on CVD and all-cause mortality was also assessed. We further explored this interaction effect in subgroups of age and BMI. The evaluation indexes were odds ratios (ORs), hazard ratios (HRs), and 95% confidence intervals (CIs). Among 13,699 eligible patients, 1,947 had CVD, and 1,560 died from all cause. After adjusting for covariates, patients who had high sedentary time seemed to have both high odds of CVD [OR=1.24, 95%CI: (1.06-1.44)] and high risk of all-cause mortality [HR=1.20, 95%CI: (1.06-1.37)]. Also, insufficiently active was linked to high odds of CVD [OR=1.24, 95%CI: (1.05-1.46)] as well as high risk of all-cause mortality [HR=1.32, 95%CI: (1.15-1.51)]. High sedentary time and insufficiently active had an interaction effect on both high odds of CVD [OR=1.44, 95%CI: (1.20-1.73)] and high risk of all-cause mortality [HR=1.48, 95%CI: (1.24-1.76)]. Patients with different age and BMI levels all need to focus on the potential CVD/mortality risk of high sedentary time and low physical activity (all P<0.05). Reducing sedentary time combined with increasing physical activity may benefit to health through reducing both the risk of CVD and all-cause mortality in middle-aged and older adults with overweight or obesity.